THE INFLUENCE OF GLOBAL GOLD PRICE VOLATILITY AND ECONOMIC UNCERTAINTY ON INVESTMENT DECISIONS AT PEGADAIAN DIGITAL CP GUNUNGSITOLI: THE ROLE OF FEAR OF MISSING OUT (FOMO) IN THE BEHAVIORAL FINANCE PERSPECTIVE - Ulfa Mardiah Gea; Syafrida Hani (Universitas La Tansa Mashiro, 2026)
Global economic instability and the surge in gold prices over recent years have driven changes in retail investor behavior, particularly in digital-based financial services. This study aims to examine the influence of gold commodity volatility and economic sector uncertainty on investment decisions of Pegadaian Digital CP Gunungsitoli customers, by placing Fear of Missing Out (FOMO) as a moderating variable within the behavioral finance perspective. This quantitative study involved 110 respondents randomly selected from the active customer population, with data analysis using multiple regression and Moderated Regression Analysis (MRA). The results show that simultaneously, both independent variables contribute significantly to investment decisions. In partial testing, only economic uncertainty proved significant (p = 0.002), while gold volatility was at a marginal threshold (p = 0.051). In the moderation test, FOMO was found unable to moderate the relationship between gold volatility and investment decisions (p = 0.642). However, FOMO positively and significantly strengthens the influence of economic uncertainty on investment decisions (p = 0.021; β = 0.581), with the model's explanatory contribution reaching 46.4 percent. These findings indicate that psychological factors such as FOMO are more responsive to macroeconomic uncertainty compared to commodity price fluctuations, suggesting that financial institutions should strengthen literacy based on behavioral bias management to encourage more rational decision-making